2006
DOI: 10.1103/physrevb.73.205415
|View full text |Cite
|
Sign up to set email alerts
|

Heat flow in nonlinear molecular junctions: Master equation analysis

Abstract: We investigate the heat conduction properties of molecular junctions comprising anharmonic interactions. We find that nonlinear interactions can lead to novel phenomena: negative differential thermal conductance and heat rectification. Based on analytically solvable models we derive an expression for the heat current that clearly reflects the interplay between anharmonic interactions, strengths of coupling to the thermal reservoirs, and junction asymmetry. This expression indicates that negative differential t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
248
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 151 publications
(261 citation statements)
references
References 48 publications
11
248
2
Order By: Relevance
“…We have recently extended the NIBA to the out-of-equilibrium two-bath case, considering harmonic environments of different temperatures [19,20,25]. Next we further point out that this extension holds for spin environments.…”
Section: B Niba Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently extended the NIBA to the out-of-equilibrium two-bath case, considering harmonic environments of different temperatures [19,20,25]. Next we further point out that this extension holds for spin environments.…”
Section: B Niba Equationsmentioning
confidence: 99%
“…Given the complex dissipative dynamics observed in the single-bath model, it is not surprising that the related out-of-equilibrium version exhibits a rich transport behavior [21][22][23][24]. We have recently extended the non-interacting blip approximation [4,8,9] and studied heat transport characteristics in the two-bath spin-boson model in the non-adiabatic regime [19,20,25]: We have validated the heat exchange fluctuation theorem in this many-body model and demonstrated that the heat current can display a significant negative differential thermal conductance (NDTC). To understand heat transport in actual nanostructures, it is of interest to explore transport behavior between other reservoirs, particularly considering anharmonic environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the QME as described here can be used to examine a range of transport problems, by turning on/off different reservoirs. Besides the analysis of inelastic electronic conduction with anharmonic modes, one can use this method and study the operation of phononthermoelectric transistors 53 and phononic thermal junctions with harmonic and anharmonic local modes, to demonstrate nonlinear function such as thermal rectification and negative differential thermal conductance 62 . To derive Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions baths' modes in resonance with the subsystem frequencies are populated, responsible for the subsystem excitation and relaxation processes. This resonance energy transfer process can be treated within the BornMarkov approximation scheme [42,43]. In Sec.…”
Section: Modelmentioning
confidence: 99%